2016
DOI: 10.1093/neuonc/now119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-wake disturbance in patients with brain tumors

Abstract: Sleep-wake disturbances are defined as perceived or actual alterations in sleep that result in impaired daytime functioning. Unlike other cancers, there is limited information about sleep-wake disturbances in adults with primary brain tumors throughout the illness trajectory. Sleep-wake disturbance is among the most severe and common symptoms reported by primary brain-tumor patients, particularly those undergoing radiation therapy. As with other cancers and neurologic illness, sleep-wake disturbance may also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 114 publications
2
63
0
2
Order By: Relevance
“…Stupp et al (2005) found that the median survival of patients receiving TMZ in addition to RT was 14.6 months as compared with 12.1 months among those who were assigned to RT alone [39]. However, despite the benefits, the treatment with TMZ can entail in some immediate side effects such as nausea, vomiting, lymphopenia, neutropenia, thrombocytopenia, fatigue, disturbed sleep and depression [40,41,42].…”
Section: Nose-to-brain Drug Deliverymentioning
confidence: 99%
“…Stupp et al (2005) found that the median survival of patients receiving TMZ in addition to RT was 14.6 months as compared with 12.1 months among those who were assigned to RT alone [39]. However, despite the benefits, the treatment with TMZ can entail in some immediate side effects such as nausea, vomiting, lymphopenia, neutropenia, thrombocytopenia, fatigue, disturbed sleep and depression [40,41,42].…”
Section: Nose-to-brain Drug Deliverymentioning
confidence: 99%
“…Damage to structures in the brainstem and posterior fossa involved in control of breathing may lead to central sleep apnea and hypoventilation [8,30,31]. Sleep problems are a significant factor negatively impacting quality of life in cancer survivors but often go under recognized and under reported [21,32]. In the following sections, we will review the prevalence and etiologies of various sleep problems reported by children with CNS tumors and discuss our approach to screening, diagnosis, and management.…”
Section: Pediatric Brain Tumors and Sleepmentioning
confidence: 99%
“…However, data remains mixed, as recent prospective surveys of pediatric brain tumor survivors found no association between tumor location and EDS [33,35]. Other reported risk factors for development of EDS include obesity [26,36], exposure to cranial radiation therapy [32,34], and use of antiepileptic medications [34].…”
Section: Excessive Daytime Sleepiness and Narcolepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Нередко у таких пациентов имеются трудности с засыпанием и поддержанием сна. Его низкая эффективность, ран-нее пробуждение и другие нарушения сна [6] становятся хроническими и сохраняются продолжительное время после завершения противоопухолевой терапии. Поэтому изучение механизмов нарушения сна и изменений в биоэлектрической активности мозга во время сна имеют важное значение для разработки программ нейрореабилитации у пациентов с опухолями головного мозга.…”
unclassified